(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article analyzes modern approaches to training nursing managers and developing information systems (IS) for effective nursing staff management. Innovative educational models integrating leadership, management, and digital competencies are discussed, as well as their impact on improving the quality of medical care. Particular attention is paid to information systems, including HL-7 and OpenEHR standards, which optimize resource management, reduce administrative burdens, and facilitate data-driven decision-making. The synergy between manager training and information system implementation, which contributes to the sustainability of healthcare systems, is emphasized. Based on an analysis of scientific literature, including Uzbek sources, and practical examples, key areas for the development of nursing management in the context of digitalization are identified, as well as prospects for their implementation in national healthcare systems.